The Effect of Complementary and Alternative Medicine on Subfertile Women with In Vitro Fertilization. (16th January 2014) - Zhang, Yuehui; Fu, Yiman; Han, Fengjuan; Kuang, Hongying; Hu, Min; Wu, Xiaoke
Abstract : About 10–15% of couples have difficulty conceiving at some point in their reproductive lives and thus have to seek specialist fertility care. One of the most commonly used treatment options is in vitro fertilization (IVF) and its related expansions. Despite many recent technological advances, the average IVF live birth rate per single initiated cycle is still only 30%. Consequently, there is a need to find new therapies to promote the efficiency of the procedure. Many patients have turned to complementary and alternative medical (CAM) treatments as an adjuvant therapy to improve their chances of success when they undergo IVF treatment. At present, several CAM methods have been used in infertile couples with IVF, which has achieved obvious effects. However, biologically plausible mechanisms of the action of CAM for IVF have not been systematically reviewed. This review briefly summarizes the current progress of the impact of CAM on the outcomes of IVF and introduces the mechanisms.